RESPON PERTUMBUHAN DAN HASIL TIGA VARIETAS KACANG TANAH (Arachis hypogaea L.) AKIBAT PERLAKUAN JARAK TANAM - E. Tadjudin; Ahmad Faaiziyn (Agroswagati Jurnal Agronomi, 2017)
This study aims to: (1) the effect of the combination of plant spacing and varieties on the growth and result of peanuts, (2) determine the varieties and spacing gives the best effect among the three varieties on growth and peanut result, (3) determine how the correlation among the components of growth and result of peanuts. The experiment was conducted in UPTD Seed Crops Development Center (BPBD) in Plumbon Cirebon regency, West Java province, from March to June 2016.The studies conducted by using a randomized block design (RAK) combination model. The treatment consists of two factors, namely peanut varieties and spacing repeated 3 times. Then treatment combination model as follows: A (varieties jerapah and a spacing of 40 cm x 20 cm), B (varieties jerapah and a spacing of 40 cm x 25 cm), C (varieties jerapah and a spacing of 40 cm x 30 cm), D (varieties maja 1 and a spacing of 40 cm x 20 cm), E (varieties maja 1 and a spacing of 40 cm x 25 cm), F (varieties maja 1 and a spacing of 40 cm x 30 cm), G (varieties maja 2 and spacing of 40 cm x 20 cm), H (varieties maja 2 and a spacing of 40 cm x 25 cm) and I (varieties maja 2 and a spacing of 40 cm x 30 cm).The results showed that: (1) there is a combined effect of plant spacing and varieties of the plant height ages of 21 and 35 days after planting, leaf number aged 21 and 35 days after planting, leaf area index age of 35 HST, root volume age 35 HST, dry biomass of plants per clumps age 35 HST, pod fresh weight per hill and per plot, weight of dry pods per hill and per plot. While the number of pods per hill and a weight of 100 dry seeds no real effect, (2) treatment D (varieties maja 1 and a spacing of 40 x 20 cm) with the result 1,1 ton/ha, E (varieties maja 1 and a spacing of 40 x 25 cm) with the result 1,2 ton/ha, F (varieties maja 1 and a spacing of 40 x 30 cm) with the result 1,1 ton/ha and G (varieties maja 2 and a spacing of 40 x 20 cm) with the result 1,0 ton/ha showed the best effect on weight of dry pods per plot, (3) there was no correlation between plant height ages of 21 and 35 HST , number of leaves ages of 21 and 35 days after planting, leaf area index age of 35 HST, HST 35 root volume, dry biomass of plants per clump age 35 HST by weight of dry pods per plot.